2022
DOI: 10.1111/1753-6405.13241
|View full text |Cite
|
Sign up to set email alerts
|

Nip allergies in the Bub: a qualitative study for a public health approach to infant feeding for allergy prevention

Abstract: Objective: To identify a brand, key messages and resources to underpin a public health approach to food allergy prevention. Methods: A focus group design was used to explore perceptions and opinions of potential brands, infant feeding messages and resources for providing standardised food allergy prevention information. Focus groups were conducted in February 2018 using interview guides and were transcribed verbatim. A content analysis of the transcripts was undertaken using thematic analysis software. The Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(81 reference statements)
0
5
0
Order By: Relevance
“… 25 When a parent responds that he or she has not introduced peanut, SmartStartAllergy sends a text message indicating that there is evidence to support peanut introduction to prevent development of peanut allergy and a link to the NAITB website is provided. A previous study reported that a website providing information about infant feeding for allergy prevention containing the ASCIA logo would be considered credible by parents 16 and that web-based information is a preferred method of accessing information. 16 , 26 A key difference between the weblink provided by SmartStartAllergy and the BabyEATS study 25 is that the link provided by SmartStartAllergy is a link to the NAITB website, which was developed specifically for parents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 25 When a parent responds that he or she has not introduced peanut, SmartStartAllergy sends a text message indicating that there is evidence to support peanut introduction to prevent development of peanut allergy and a link to the NAITB website is provided. A previous study reported that a website providing information about infant feeding for allergy prevention containing the ASCIA logo would be considered credible by parents 16 and that web-based information is a preferred method of accessing information. 16 , 26 A key difference between the weblink provided by SmartStartAllergy and the BabyEATS study 25 is that the link provided by SmartStartAllergy is a link to the NAITB website, which was developed specifically for parents.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that a website providing information about infant feeding for allergy prevention containing the ASCIA logo would be considered credible by parents 16 and that web-based information is a preferred method of accessing information. 16 , 26 A key difference between the weblink provided by SmartStartAllergy and the BabyEATS study 25 is that the link provided by SmartStartAllergy is a link to the NAITB website, which was developed specifically for parents. 16 Furthermore, general practitioners were considered a useful source of information by mothers and partners, with 83.2% reporting that information coming from a trusted and reliable source is very important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before peanut introduction, the guidelines recommend introducing non-allergic foods to determine infants' readiness for solid foods 11. Recording a food diary of new foods may be helpful for parents 32…”
Section: Preventionmentioning
confidence: 99%